تتبع التغيرات المكانية للغطاء النباتي في بلدية تاجوراء للفترة من 1984م – 2024م باستخدام مؤشر MSAVI - الشامخ, نعيمة موسى (Al-Qurtas, 2025)
تتبع التغيرات المكانية للغطاء النباتي في بلدية تاجوراء للفترة من 1984م – 2024م باستخدام مؤشر MSAVI